Uncertainties in gas-phase atmospheric iodine chemistry - Sommariva, Roberto; Bloss, William; Glasow, Roland von (Atmospheric environment, 2012)
We present a comprehensive chemical mechanism for gas-phase iodine, to be used for modelling tropospheric chemistry. The mechanism has been compiled from evaluated data and individual literature studies, where available; a number of key processes have not been studied experimentally or theoretically and in these cases estimations have been made. The uncertainty associated with these assumptions is evaluated. We analyze the mechanism using a box-model under a variety of boundary layer scenarios - representative of environments where iodine species have been observed - to study the response of the chemical system to changes in the kinetic parameters of selected reactions. We focus in particular on key species such as IO, OIO, INO3 and I2Oy and the impact of iodine chemistry on ozone formation and HOx levels. The results indicate that the chemical system is most sensitive to reactions leading to comparatively stable iodine compounds, which should be a focus of future laboratory studies.